MANAJEMEN KURIKULUM: Sebuah Kajian Teoritis - Nasbi, Ibrahim (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Curriculum management is a system of curriculum management that is cooperative, comprehensive, systemic, and systematic in order to realize the achievement of curriculum objectives. A good curriculum is a curriculum that follows the development of science and technology based on society. The management of a curriculum determines success and failure in education. Therefore, the responsibility of educational institutions and all education stakeholders should have the same vision in planning, organizing, implementing and evaluating a curriculum.